Factors Associated With Return to Work After Surgery for Degenerative Cervical Spondylotic Myelopathy: Cohort Analysis From the Canadian Spine Outcomes and Research Network. Issue 4 (May 2022) - Romagna, Alexander; Wilson, Jefferson R.; Jacobs, W. Bradley; Johnson, Michael G.; Bailey, Christopher S.; Christie, Sean; Paquet, Jerome; Nataraj, Andrew; Cadotte, David W.; Manson, Neil; Hall, Hamilton; Thomas, Kenneth C.; et al.
Study design: Retrosepctive analysis of prospectively collected data from the multicentre Canadian Surgical Spine Registry (CSORN). Objective: Degenerative cervical myelopathy (DCM) is the most common cause of spinal cord dysfunction in North America. Few studies have evaluated return to work (RTW) rates after DCM surgery. Our goals were to determine rates and factors associated with postoperative RTW in surgically managed patients with DCM. Methods: Data was derived from the prospective, multicenter Canadian Spine Outcomes and Research Network (CSORN). From this cohort, we included all nonretired patients with at least 1-year follow-up. The RTW rate was defined as the proportion of patients with active employment at 1 year from the time of surgery. Unadjusted and adjusted analyses were used to identify patient characteristics, disease, and treatment variables associated with RTW. Results: Of 213 surgically treated DCM patients, 126 met eligibility, with 49% working and 51% not working in the immediate period before surgery; 102 had 12-month follow-up data. In both the unadjusted and the adjusted analyses working preoperatively and an anterior approach were associated with a higher postoperative RTW ( P < .05), there were no significant differences between the postoperative employment groups with respect to age, gender, preoperative mJOA (modified Japanese Orthopaedic Association) score, and duration of symptoms ( P > .05). Active preoperative employment (odds ratio = 15.4, 95% confidence interval = 4.5, 52.4) and anterior surgical procedures (odds ratio = 4.7, 95% confidence interval = 1.2, 19.6) were associated with greater odds of RTW at 1 year. Conclusions: The majority of nonretired patients undergoing surgery for DCM had returned to work 12 months after surgery; active preoperative employment and anterior surgical approach were associated with RTW in this analysis.